Paediatric acute respiratory infections: a case series based clinical analysis and recommendations in accordance with WHO guidelines - Krishna, Gautham; Rajan, Nithin; Asokan, Aparnna B.; Mohan, Arya B. (International Journal of Contemporary Pediatrics, 2023)
Pneumonia is one of the most common respiratory disorder across the globe. Pneumonia is a leading cause of morbidity and mortality in children younger than the age of 5 years. Bronchopneumonia is one of the typically seen presentation of pneumonia occurring mainly in the pediatric population. If not treated promptly, it might become life-threatening. Since pneumonia is associated with significant morbidity and mortality, promptly diagnosing pneumonia, correctly recognizing any complications or underlying conditions, and appropriately treating patients are of prime importance. This case series aims at providing a discussion of the diagnosis, management and comprehensive plan of care for bronchopneumonia in pediatric population.